Кримінальна відповідальність військовослужбовців за викрадення, привласнення зброї, військового майна, бойових припасів: історико-правовий аспект - Русанова, Л. В.; Rusanova, L. V. (Вісник Кримінологічної асоціації України. - 2017. - № 2 (16). - С. 210-220, 2017)
Стаття присвячена вивченню ґенези встановлення у кримінальному законодавстві норми про відповідальність військовослужбовців за викрадення, привласнення зброї, військового майна, бойових припасів. З’ясовано, що першим актом, яким криміналізується цей злочин, було Соборне Уложення 1649 р., наступним стали «Права, за якими судиться малоросійський народ», а також те, що КК УРСР 1960 р. включав майже аналогічну норму тій, що закріплена в сучасному КК України.

The article is focused on studying the history of the establishment of the liability for theft, embezzlement of weapons, military property, ammunition within criminal legislation. It has been found out that the first act, which provided the liability for this crime, was the Code of Law of 1649, and hence its adoption was a significant event in the history of criminal legislation. The Code has clearly defined sanctions for military crimes, including the theft, embezzlement of weapons, military property, etc. It is also important that for the first time the author has accomplished the di-vision of the crimes of “warriors” into the groups: I – actions defined as military treason (“informing the enemy the data about the army, the transfer to the enemy side, the handing over to the enemy of the city”, etc.); II – crimes against life, health and dignity, caused by warriors during campaigns (murder, rape, bodily harm, etc.); ІІІ – crimes against the property of local residents (theft, robbery, devastation of yards and cities, seizure of grain stocks), and IV – crimes against the property of their comrades (theft of weapons and horses), they included the Art. 28 of the Section VII “On the Service of All Warriors of the Moscow State”. Thus, during the studied period, the list of acts that were under criminal liability is almost the same as that enshrined in the Section XIX of the Criminal Code of Ukraine. The next act was “The Rights that are the Basis for the Judiciary of the Little Russian People”. Thus, the the list (types) of war crimes (which included the unauthorized abandonment of military service without valid reasons, the absence for military service without valid reasons (p. 2 of the clause 11), murder, robbery, rape of civilians during a campaign or march-off (p. 1 of the clause 15); attack, injuring each other, disputes, fightings, (p. 2 of the clause 15), borrowing of weapons, the horse to show the chief (the clause 16), etc.) contained the clause 20, which dealt with the theft of weapons. It has been established that the Military clause of Peter I, which contains the norms of only criminal law, is actually the Military Criminal Code without the Ge-neral Part. Thus, the Section 6 “On Military Ammunition, Weapons, Uniform, Their Theft and Its Negligence”, which specifies the duties of military servicemen regarding the handling of their weapons, as well as the sanctions imposed for their violation, contains the clause 66, which deals with the possession of military property by the way of fraud (money, food products, uniform). It is believed that this clause establishes provisions similar to the p. 1 of the Art. 410 of the Criminal Code of Ukraine. In Soviet times, the first special norm that established the liability for one types of theft – was the embezzlement of weapons of military servicemen, appeared in the Criminal Code of the RSFSR in 1922. More fully, the liability for the theft of weapons was enshrined in the Criminal Code of Ukrainian SSR in 1960, which was almost the same as the current one. It has been confirmed that military and criminal legislation from the time of its origin was constantly changed, acquired sufficiently structured form; the very concept of the “war crime” was improved (more deeply and objectively interpreted).

Статья посвящена изучению генезиса установления в уголовном законодательстве нормы об ответственности военнослужащих за похищение, присвоение оружия, военного имущества, боевых припасов. Выяснено, что первым актом, в соответствие с которым криминализируется это преступление, было Соборное Уложение 1649 г., следующим стали «Права, по которым судится малороссийский народ», а также то, что УК УССР 1960 г. включал почти аналогичную норму той, что закреплена в современном УК Украины.
Criminal liability of military servicemen for theft, embezzlement of weapons, military property, ammunition: historical and legal aspect
Уголовная ответственность военнослужащих за похищение, присвоение оружия, военного имущества, боеприпасов: историко-правовой аспект
Русанова, Л. В. Кримінальна відповідальність військовослужбовців за викрадення, привласнення зброї, військового майна, бойових припасів: історико-правовий аспект / Людмила Василівна Русанова // Вісник Кримінологічної асоціації України. - 2017. - № 2 (16). - С. 210-220.
Rusanova, L. V. (2017), “Criminal Liability of Military Servicemen for Theft, Embezzlement of Weapons, Military Property, Ammunition: Historical and Legal Aspect” [Kryminalna vidpovidalnist viiskovosluzhbovtsiv za vykradennia, pryvlasnennia zbroi, viiskovoho maina, boiovykh prypasiv: istoryko-pravovyi aspekt], Visnyk Kryminolohichnoi asotsiatsii Ukrainy, No. 2 (16), pp. 210–220.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Україна. Ukraine. Украина; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; військово-кримінальне законодавство; military and criminal legislation; военно-уголовное законодательство; військові злочини; military crimes; военные преступления; кримінальна відповідальність; criminal liability; уголовная ответственность; військовослужбовці; military serviceman; военнослужащие; похищение, присвоение оружия, военного имущества, боеприпасов; theft, embezzlement of weapons, military property, ammunition; викрадення, привласнення зброї, військового майна, бойових припасів; зброя; військове майно; бойові припаси; weapons; ammunition; военное имущество; боеприпасы